REFORMASI MANAJEMEN KEUANGAN SEKTOR PUBLIK - Mustafa Hasbar (AkMen JURNAL ILMIAH, 2011)
The financial management area since enactment of the Act OtonomiDaerah, still very far from expectations. Implementation of regional financial governance still needs to be reformed, so that the financial management area runs out transparent, accountable and accountable. Local financial management sourced from local fiscal management, still reflect a discrepancy with what has been underlined in the rule of law. This can be seen from the results of audits by BPK to local finance, which in terms of which are still very many areas that get a fair opinion with the exception that not even a little disclaimer. This also happens in some urban districts in South Sulawesi.